"Agglomeration of flows": Case of migration ties between the Arctic and the southern regions of Russia. Issue 1 (26th March 2021) - Zamyatina, Nadezhda; Goncharov, Ruslan
Abstract: Although the northern regions of Russia are relatively sparsely populated, they account for a significant portion of all‐Russian migrations. Contrary to the widespread stereotype that these migrations are based on the return of people who migrated to the North and Arctic during the Soviet era, there is a two‐way migration (although outflow from the North in many cases prevails). At the same time, a number of pairs of regions (northern—southern) have developed, migration between which is especially strong. To identify them, the method of calculating Migration Indices of Proportionality of (spatial) Structure was used. It is based on calculating migration volumes in a model based on the hypothesis of a uniform distribution of migration flows. The discrepancy between the real volumes of migration and the model ones makes it possible to identify extraordinary flows between a couple of regions. Examples of such flows are: Murmansk Oblast'–Novgorod Oblast', Magadan Oblast'—Belgorod Oblast', Kamchatka Oblast'—Kaliningrad Oblast', Yamal‐Nenets Autonomous Okrug—Republic of Bashkortostan, etc. The history of the "exit" of migrants to the North during the Soviet era, but also to a large extent with the unique institutional features of individual regions of Russia. Resumen: Aunque las regiones del norte de Rusia están relativamente poco pobladas, representan una parte importante de las migraciones de toda Rusia. En contra del estereotipo generalizado de que estas migraciones se basan en el retorno de personas que emigraron al Norte y al Ártico durante la época soviética, existe una migración bidireccional (aunque en muchos casos predomina el movimiento hacia afuera desde el Norte). Al mismo tiempo, se han desarrollado una serie de pares de regiones (norte—sur), cuya migración entre ellas es especialmente fuerte. Para identificar estos pares, se utilizó el método de cálculo de los Índices de Migración de la Proporcionalidad Estructural (espacial). Este método se basa en el cálculo de los volúmenes de migración en un modelo basado en la hipótesis de una distribución uniforme de los flujos migratorios. La discrepancia entre los volúmenes reales de migración y los del modelo permite identificar flujos extraordinarios entre un par de regiones. Ejemplos de estos flujos son: Región de Murmansk–Óblast de Novgorod, Región de Magadán–Óblast de Belgorod, Región de Kamchatka–Óblast de Kaliningrado, Distrito Autónomo de Yamal‐Nenets–República de Bashkortostán, entre otras. Estos se explican por la historia de las "partidas" de emigrantes hacia el Norte durante la época soviética, pero también en gran medida por las características institucionales únicas de cada región de Rusia. 抄録: ロシア北部の地域はかなり人口が少ないが、ロシアのすべての移動の大部分を占めている。こうした移動は、ソ連時代に北部と北極圏へ移動した人々の帰還によるという一般的な固定観念とは反対に、双方向の移動がある(しかし、多くの場合は北部からの流出が優勢である)。同時に、いくつかの地域(北部‐南部)のペアが形成され、その間の移動が特に多い。それを確認するために、(空間)構造の均衡性の移動指標を計算する方法を用いた。この方法は、移動フローの均等な分布の仮説に基づくモデルにおける移動フローの計算に基づいている。実際の移動量とモデルの移動量との不一致により、地域間の異常なフローを認識できる。ムルマンスク州‐ノヴゴロド州、マガダン州‐ベルゴロド州、カムチャツカ州‐カリーニングラード州、ヤマロ・ネネツ自治管区‐バシコルトスタン共和国などがその例である。ソ連時代の北部への移住者の「出口」の歴史であるが、その大部分はロシアの各地域に特有な制度的な特徴がある。